2022
DOI: 10.3390/cells11030413
|View full text |Cite
|
Sign up to set email alerts
|

Reprogramming of Lipid Metabolism in Lung Cancer: An Overview with Focus on EGFR-Mutated Non-Small Cell Lung Cancer

Abstract: Lung cancer is the leading cause of cancer deaths worldwide. Most of lung cancer cases are classified as non-small cell lung cancers (NSCLC). EGFR has become an important therapeutic target for the treatment of NSCLC patients, and inhibitors targeting the kinase domain of EGFR are currently used in clinical settings. Recently, an increasing interest has emerged toward understanding the mechanisms and biological consequences associated with lipid reprogramming in cancer. Increased uptake, synthesis, oxidation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 120 publications
(143 reference statements)
1
24
0
1
Order By: Relevance
“…Recent studies have shown that abnormal metabolite or intermediate metabolism in cancer may regulate immune cell proliferation, differentiation, activation, and function ( 12 , 13 ). Metabolic reprogramming has been studied in a range of tumors, including lung cancer ( 14 ), liver cancer ( 15 ), and glioma ( 16 ). However, metabolic reprogramming and immune response in HSCC have not been researched.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that abnormal metabolite or intermediate metabolism in cancer may regulate immune cell proliferation, differentiation, activation, and function ( 12 , 13 ). Metabolic reprogramming has been studied in a range of tumors, including lung cancer ( 14 ), liver cancer ( 15 ), and glioma ( 16 ). However, metabolic reprogramming and immune response in HSCC have not been researched.…”
Section: Introductionmentioning
confidence: 99%
“…But reovirus is also undergoing clinical testing as a candidate cancer therapeutic since it replicates efficiently in cancer cells. In general, untransformed cells preferentially obtain fatty acids from extracellular sources, while metabolic changes in cancer cells often support enhanced de novo fatty acid synthesis and LD formation [ 66 , 67 ]. While major determinants of enteric and tumor specificity have been described [ 3 , 20 , 21 , 68 70 ], could additional host factors, such as LD abundance, also contribute to how well reovirus thrives in these environments?…”
Section: Discussionmentioning
confidence: 99%
“…But reovirus is also undergoing clinical testing as a candidate cancer therapeutic since it replicates efficiently in cancer cells. In general, untransformed cells preferentially obtain fatty acids from extracellular sources, while metabolic changes in cancer cells often support enhanced de novo fatty acid synthesis and LD formation 64,65 . While major determinants of enteric and tumor specificity have been described [19][20][21][66][67][68] , could additional host factors, such as LD abundance, also contribute to how well reovirus thrives in these environments?…”
Section: Discussionmentioning
confidence: 99%